2022
DOI: 10.3390/ijerph19138155
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercise on Acute Immune Responses in Relative Leisure-Deprived People Living with HIV/AIDS: A Pilot Study

Abstract: Exercise training involving exercises of optimal intensity and duration improves psychological and medical variables in relative leisure-deprived people living with HIV/AIDS. This study aimed to analyze associated psychological variables and the effect of exercise intensity and duration on immune responses in relative leisure-deprived people infected with HIV. The participants completed different moderate-intensity exercises (30 min (60–80% HRmax) and 45 min (60–80% HRmax)) and high-intensity exercise for 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Owing to the low amount of physical activity and low fitness level at baseline, the exercise itself may have been stressful to the participants. In a previous study conducted in our laboratory, stress responses to acute treadmill exercises such as high cortisol levels were also observed in PLWHA [ 23 ]. The form of exercise performed can play an important role in increasing interest in exercise.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Owing to the low amount of physical activity and low fitness level at baseline, the exercise itself may have been stressful to the participants. In a previous study conducted in our laboratory, stress responses to acute treadmill exercises such as high cortisol levels were also observed in PLWHA [ 23 ]. The form of exercise performed can play an important role in increasing interest in exercise.…”
Section: Discussionmentioning
confidence: 93%
“…A detailed selection process of the exercise intensity and duration was presented in the earlier publication of the study results [ 23 ]. Moderate-intensity (60-80% HRmax) exercise was used for exercise training.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With more PLWH able to remain undetected and reduce the severe impairment HIV can have on the immune system, it is plausible that HIIT would not pose a serious health risk any more than it would for individuals without HIV. In recent years, some studies have compared high-intensity aerobic exercise and moderateintensity aerobic exercise (14)(15)(16)(17)(18)(19). These studies have shown that a high-intensity modality and dosage was just as safe as moderate-intensity exercise in which both have shown to improve strength, body composition, and V ˙O2 peak (16,17).…”
Section: High-intensity Physical Activity and Exercise Research With ...mentioning
confidence: 99%